2019
DOI: 10.1084/jem.20181394
|View full text |Cite
|
Sign up to set email alerts
|

Lamin B1 loss promotes lung cancer development and metastasis by epigenetic derepression of RET

Abstract: Although abnormal nuclear structure is an important criterion for cancer diagnostics, remarkably little is known about its relationship to tumor development. Here we report that loss of lamin B1, a determinant of nuclear architecture, plays a key role in lung cancer. We found that lamin B1 levels were reduced in lung cancer patients. Lamin B1 silencing in lung epithelial cells promoted epithelial–mesenchymal transition, cell migration, tumor growth, and metastasis. Mechanistically, we show that lamin B1 recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 80 publications
2
35
1
1
Order By: Relevance
“…We showed IL-3Rα expression in murine lung epithelial-12 (MLE-12, hereafter "MLE") cells and RAW264.7 cells ( Figure 1A and Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.133652DS1). IL-3Rα transcript was also present in RNA-Seq experiments from MLE cells (Gene Expression Omnibus accession GSE94680) (22). MLE cells were treated with CHX, and IL-3Rα half-life was observed to be approximately 6 hours; additionally, we found CHX-induced IL-3Rα degradation was prevented by the proteasome inhibitor MG132 but not by the lysosomal inhibitor leupeptin ( Figure 1A).…”
Section: Resultsmentioning
confidence: 81%
“…We showed IL-3Rα expression in murine lung epithelial-12 (MLE-12, hereafter "MLE") cells and RAW264.7 cells ( Figure 1A and Supplemental Figure 1A; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.133652DS1). IL-3Rα transcript was also present in RNA-Seq experiments from MLE cells (Gene Expression Omnibus accession GSE94680) (22). MLE cells were treated with CHX, and IL-3Rα half-life was observed to be approximately 6 hours; additionally, we found CHX-induced IL-3Rα degradation was prevented by the proteasome inhibitor MG132 but not by the lysosomal inhibitor leupeptin ( Figure 1A).…”
Section: Resultsmentioning
confidence: 81%
“…Cancer biologist and many researchers ascribe the relationship between abnormal expression of lamin and cancer subtype by examining alterations in lamin expression in different types of cancers. Loss of lamin B1 plays a key role in lung cancer and it has been demonstrated that lamin B1 levels were decreased in patients of lung cancer 40 . Epithelial-mesenchymal transition, tumor growth, cell migration and metastasis is promoted by lamin B1 silencing in lung epithelial cells 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Loss of lamin B1 plays a key role in lung cancer and it has been demonstrated that lamin B1 levels were decreased in patients of lung cancer 40 . Epithelial-mesenchymal transition, tumor growth, cell migration and metastasis is promoted by lamin B1 silencing in lung epithelial cells 40 . It was shown that lamin B1 is decreased in murine and primary human cells when they are induced to senescence by replicative exhaustion, DNA damage, or oncogene expression 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Lamin B1 is also important for proper migration of mouse cardioepithelial cells during heart development [ 15 ]. However, analyses of cancer cell migration identified a migration inhibitory role for lamin B1 in lung cancer cells [ 16 ], while a migration promoting activity was found for lamin B1 in pancreatic cancer cells [ 17 ]. Lamin A analyses found that increased levels of lamin A inhibit cancer cell migration [ 18 , 19 , 20 , 21 , 22 ], while reduced lamin A levels accelerate cell migration rate [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major mechanism by which lamins affect cell migration is thought to be by altering the stiffness of the nuclear envelope: A-type lamins are thought to generate a stiffer filamentous network than B-type lamins [ 19 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In addition, epigenetic effects of lamin B1 were suggested to cause its inhibitory effect on lung cancer cell migration [ 16 ].…”
Section: Introductionmentioning
confidence: 99%